2020
DOI: 10.5798/dicletip.706005
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CDX2 Expression Adversely Effect On Prognosis Of Patients With Colorectal Cancer

Abstract: Objective: Since colorectal cancers (CRC) are tumors with heterogeneous biological behavior, prediction of their prognosis remains challenging. Caudal-related homeobox gene 2 (CDX2), which has important roles in the development and maintenance of intestines, is thought to have tumor suppressing effect on CRCs. The aim of this study was to investigate the prognostic significance of decreased-CDX2 expression. Method: This retrospective study included 224 patients diagnosed with CRC between 2009 and 2014. Paraffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Similarly, other studies observed low CDX2 expression is significantly correlated with poor differentiation grade. Besides, other studies found the same result regarding the association between low expression of this protein and high grade of CRC (Bonetti et al 2017;Çalik et al 2020;Dalerba et al 2016;Oslen et al 2014;Shigematsu et al 2018). On the contrary, the current result was in disagreement with that reported by (Hong et al 2013;Sjoerd et al 2021).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Similarly, other studies observed low CDX2 expression is significantly correlated with poor differentiation grade. Besides, other studies found the same result regarding the association between low expression of this protein and high grade of CRC (Bonetti et al 2017;Çalik et al 2020;Dalerba et al 2016;Oslen et al 2014;Shigematsu et al 2018). On the contrary, the current result was in disagreement with that reported by (Hong et al 2013;Sjoerd et al 2021).…”
Section: Discussioncontrasting
confidence: 59%
“…Downregulation of CDX2 expression has been correlated with CRC progression, and the results of various studies suggest this gene may have tumor suppressor activity, though the extent to which this activity correlates with prognosis, patient survival, and clinicopathologic characteristics is still debatable (Cecchini et al 2019;Xu et al 2019). Previous researches have demonstrated that a low CDX2 expression is associated with a worse prognosis and shorter survival in CRC patients (Çalik et al 2020;Zheng et al 2017). Therefore, the purpose of this study was to determine whether or not CDX2 expression was associated with better outcomes for people with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple instances, researchers have demonstrated that diminished or absent CDX2 expression is associated with the aggressive behavior of CRC, characterized by invasive and poorly differentiated tumors, as well as low overall survival (OS) and disease-free progression (DFS) rates [7,9,21,31,34,[36][37][38].…”
Section: Deciphering the Relationship Between The Cdx2 And Clinicopat...mentioning
confidence: 99%
“…Although researchers have shown that there is no statistically significant correlation between the age and sex of patients and tumors exhibiting reduced or absent CDX2 gene expression, some studies have suggested a greater prevalence of CDX2-negative tumors in elderly women [34,36,37,39,40]. Concerning the primary tumor site, research suggests that tumors exhibiting diminished or negative CDX2 expression are commonly found in the right colon, including the cecum, ascending colon, and transverse colon [9,32,34,40,41].…”
Section: Deciphering the Relationship Between The Cdx2 And Clinicopat...mentioning
confidence: 99%
See 1 more Smart Citation